2001
DOI: 10.1046/j.1423-0410.2001.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of donor arm disinfection techniques

Abstract: The Medi-Flex disinfection method offers the English National Blood Service a validated, optimal 'best practice' disinfection technique and should contribute significantly to the reduction in risk of transmission of bacteria by transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 9 publications
3
87
1
3
Order By: Relevance
“…Sample collection was performed 3 and 5 days after CVC insertion, before dressing changes, using sterile and disposable swabs packaged in individual swab containers (Absorve ® , Carl, São Paulo, Brazil). The swab was previously moistened in a sterile phosphate-buffered saline (PBS buffer) containing 3% Tween-80 18 , and rubbed for 30 seconds with uniform up and down movements in a 5 cm 2 area delineated by a sterile filter paper template (Nalgon ® , Nalgon Equipamentos Científicos Ltda, São Paulo, Brazil) 19 . The swab was then placed in sterile tubes containing 1 ml of 0.9% saline solution and 8 glass beads, and transported in a thermal box to the Laboratory of Basic Research of the School of Health Sciences at UNIVÁS.…”
Section: Evaluation Of the Microbiological Culturementioning
confidence: 99%
“…Sample collection was performed 3 and 5 days after CVC insertion, before dressing changes, using sterile and disposable swabs packaged in individual swab containers (Absorve ® , Carl, São Paulo, Brazil). The swab was previously moistened in a sterile phosphate-buffered saline (PBS buffer) containing 3% Tween-80 18 , and rubbed for 30 seconds with uniform up and down movements in a 5 cm 2 area delineated by a sterile filter paper template (Nalgon ® , Nalgon Equipamentos Científicos Ltda, São Paulo, Brazil) 19 . The swab was then placed in sterile tubes containing 1 ml of 0.9% saline solution and 8 glass beads, and transported in a thermal box to the Laboratory of Basic Research of the School of Health Sciences at UNIVÁS.…”
Section: Evaluation Of the Microbiological Culturementioning
confidence: 99%
“…52,53 Recent studies exploring blood culture contamination rates of blood products have demonstrated that both the quality of the antiseptic used and/or the mode of application of the antiseptic can influence the efficacy of skin disinfection. Thus, one possibility of reducing the prevalence of blood product bacterial contamination might be to improve donor skin disinfection.…”
Section: Improving Donor Skin Disinfectionmentioning
confidence: 99%
“…Transfusion associated sepsis cases are encountered occasionally and bacterial transmission remains the major cause of acute morbidity and mortality following post transfusion infection [1][2][3][4]. Bacterial contamination of platelet products is generally the most frequent infectious risk associated with transfusion [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms of bacterial contamination of blood components include donor bacteremia, contamination during the whole blood collection procedure, contamination of the collection pack or contamination during the blood processing procedure [3,4,9]. The types of organisms isolated in these transmissions indicate that the major source of contamination is skin derived [1]. Micro organisms are present on skin of all individuals but are numerous only in relatively moist areas [9].…”
Section: Introductionmentioning
confidence: 99%